1988
DOI: 10.1111/j.1439-037x.1988.tb00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Nutzbarkeit des generativen Speicherpotentials von indeterminierten Ackerbohnengenotypen (Vicia faba L.)

Abstract: Investigations on the utilization of the generative storage potential of indeterminated field bean genotypes (Vicia faba L.) The gradation in seed yield between and within the inflorescences of a field bean plant results from a hierarchical control by way of internal competition in connection with hormonal regulation. Following this hypothesis in genotypes with different yielding capacity (2 inbred lines, 1 hybrid) the two proximal flowers/inflorescence of the nodes 3–6 (counted from the bottom of the plant) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…Stubble buckwheat had a shorter period from sowing till the end of flowering growth than from buckwheat under full-season production system, but the number of flowers in all treatments increased 5055 days after sowing and the number of formed seeds varied between 2055 seeds per plant (data not shown). In Aufhammer et al (1994) investigation the number of flowers increased from 6070 days after sowing and number of seeds varied from 60 to 100 seeds per plant. According to our and Aufhammer et al (1994) data phenological development depends on temperature sum (days °C) and day length.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Stubble buckwheat had a shorter period from sowing till the end of flowering growth than from buckwheat under full-season production system, but the number of flowers in all treatments increased 5055 days after sowing and the number of formed seeds varied between 2055 seeds per plant (data not shown). In Aufhammer et al (1994) investigation the number of flowers increased from 6070 days after sowing and number of seeds varied from 60 to 100 seeds per plant. According to our and Aufhammer et al (1994) data phenological development depends on temperature sum (days °C) and day length.…”
Section: Resultsmentioning
confidence: 94%
“…In general, early spring sowing of buckwheat, leads to higher leaf area index (LAI), total biomass and grain yield, but the growth of plants can be damaged by late frost (Aufhammer et al 1994), temperatures exceeding 17.5°C (Sugimoto and Sato 1999), or by lodging, while late sowings may suffer from lack of moisture at emergence, short assimilation period and formation of short stems. Number of flowers, flower clusters and the seed set vary with sowing date often associated with risk of water shortage (Aufhammer et al 1994, Hagiwara et al 1998, Liszewski 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Variety Pyra, which was selected from old regional cultivars, manifested the adaptation to different conditions of cultivation. The higher resistance of tetraploid variety Emka is also reported by Aufhammer et al (1994). Generally, tetraploid varieties belong to the group of varieties that are demanding and more sensitive to cultivation conditions.…”
Section: Discussionmentioning
confidence: 83%
“…Aufhammer et al (1994) reported that temperature -2°C caused severe damage to the plants and temperature -4°C caused total frost disruption of analysed plants. On the contrary Jakimenko (1982) reported partial damage at temperature -1°C and total disruption at -2°C.…”
mentioning
confidence: 99%